The Road Travelled in Europe towards the 2020 European Objectives in Education. A Spanish Perspective. (28th April 2015) - Martínez Seijo, María Luz; Torrego Seijo, Juan Carlos
Abstract : From the beginning of the European Community to the current EU there have been important steps in education cooperation between the participating countries. In this article, we analyse the facts and difficulties that influence the educational policy of the EU to reach agreements and the facts that define common work until the year 2020, mainly under the principle of subsidiarity or complementarity. We also discuss the way to work in the different administrative political systems of the EU countries, i.e. centralised, federal and decentralised countries and how these systems influence education policies. Another objective of this article is to discuss the role of National Agencies in the development of European programmes in the different administrative political systems and their structure. We analyse the European framework so that the European objectives in education can be developed in the Member States.